Evaluation of the Intake of Nitrate, Nitrite, Nitrosodiethylamine and Nitrosodimethylamine by Food Consumption - Liliana Avasilcai; Marieta Nichifor; Geanina Bireescu; Rodica Cuciureanu (EQA, 2014)
The aim of the present study was the evaluation of nitrate, nitrite, nitrosodiethylamine (NDEA) and nitrosodimethylamine (NDMA) intake by food consumption. We determined concentrations of nitrates, nitrites in 102 food samples (40 meat products, 15 fermented cheese, 25 vegetables, 22 fruits) and the concentration NDEA, NDMA in 40 meat products. Nitrates and nitrites were determined using Peter-Griess method; nitrosamines were quantified by HPLC with UV detection.  We designed vegetalian, vegetarian and conventional diets of about 2500 kcal/day.  Based of the values found, we calculated the intake of nitrates, nitrites and nitrosamines. The obtained values fits to WHO’s recommendations, except for vegetalian and conventional diet, in which the nitrate content was 3,46 respectively 1,64 times higher than the acceptable daily intake (157 mg NO3-/day).